Are Standards-based Quality Systems a Threat to the Internationalization of Teaching and Learning? - Scott Thompson-Whiteside (IAFOR Journal of Education, 2013)
This paper explores the current shift in Australia’s higher education system moving to a more explicit, standards-based quality system and its potential impact on international partnerships in teaching and learning, particularly in Asia. The new Tertiary Education Quality and Standards Agency and the underlying Higher Education Standards Framework have the potential to threaten a large number of transnational or cross-border programs delivered outside of Australia. With over one hundred and fifty thousand tertiary students studying Australian programs in Asia, the impact could be significant. It would also be significant for countries that leverage of Australian Universities to build human capacity within their country. The paper highlights the current practice of assuring equivalent and comparable academic standards in transnational education and explores how shifting to a more precise standards framework will require more explicit demonstration of standards across teaching, learning and student outcomes. If equivalent or comparable standards were to be achieved across the whole standards framework, it is likely to constrain the opportunities for internationalization and the formation of new transnational partnerships.